Implementation of the Criminal Justice System for Persons with Disabilities - Taufik Hidayat; Mahrus Ali; Arief Hidayatullah Khamainy; Nyoman Serikat Putra Jaya; Pujiyono (Indian Journal of Forensic Medicine & Toxicology, 2021)
The criminal justice system is built on the ideology of normality, a perspective that all people are physically and intellectually normal. Consequently, the process of investigation, prosecution and examination in court proceedings is only aimed at and designed for those who are normal. The existence of persons with disabilities has become marginalized and even forgotten. The rights of persons with disabilities are often violated both when they are perpetrators and witnesses/victims of criminal acts. In order for the criminal justice system to be pro for them, the medical approach should be abandoned and replaced with a social approach. Here what is needed is what the law enforcers need to fulfill at each stage of the criminal justice so that persons with disabilities have the right to a fair criminal trial. A profile assessment is necessary to determine the character, barriers and needs of persons with disabilities in the early stages of the criminal justice process.